A Comprehensive Bibliometric Analysis of Voice Commerce Research: Trends, Contributions, and Collaborations - Joseph, Arun George; Michael, Babu; Kavukattu, Nora Babu; Kartha, N.V Madhusoodanan; K, Syamkumar (International Review of Management and Marketing, 2025)
With the increasing integration of AI, machine learning, and voice-activated technologies into various commercial sectors, voice commerce has emerged as an important area of research. In this regard, the present study undertakes a bibliometric review of voice commerce research emanating between 1965 and 2024 to map the intellectual landscape, identify key contributors, and uncover emerging trends. The analysis, then, will be based on bibliographic data from Scopus, limited to journal articles and conference papers dealing with the area of interest represented by the terms "Voice" and "Commerce." This study will describe the growth and development of the field under consideration using, among others, the facilities offered by VOSviewer, CiteSpace, and Biblioshiny to analyze publication patterns, citation impact, and networks of research collaboration. Further, the research investigates the big themes of artificial intelligence, e-commerce, and consumer behavior, thus identifying the lacunae regarding ethical consideration, privacy issue, and the gap in exploring integrations of under-studied technologies. These findings provide useful insights into academics and practitioners and evidence of the dynamic nature of voice commerce research and its rising relevance globally. This analysis is supposed to be a basic reference for research and practical applications in voice commerce, which is now taking shape.